Perancangan dan Pembuatan Mesin Bending dan Notching - Muhammad Yanis; gunawan; Ricky Wahyu Pratama (Universitas Sriwijaya, 2021)
Bending and notching is a common process in manufacturing world as in vehicles chassis fabrication. But, the recent problem is the limited tools that needed to bend and notch pipes. The objective of this research is to fabricate a tool or production machine that could bend and notch pipes based on need by using three roll bending method. As for the notching angle of 0 to 60 and the diameter for notching cutting is 1 to 2 inch. There are some calculations on machine structure by using solidworks simulation such as stress analysis, von mises and factor of safety. There are three trials in bending process such as deflection from 1, 2 and 3 cm and on the other side, notching trials start from 0 to 60 . This notching and bending machine created with two functions. The bending process is conducted in the middle part while the notching process is in the top part of the machine. This machine has 70 cm length, 50 cm wide and 120 cm height and the total amount of cost spent for this machine is Rp. 9.009.500.